Exclusive Breastfeeding Counseling among Postpartum Mother: Penyuluhan ASI Eksklusif pada Ibu Nifas - Yuni Kristiani Tumani; Enggar Enggar; Ni Made Rosiyana; Novita Lestari (Jurnal Pengabdian Bidan Nasuha, 2022)
Introduction: The coverage of infants receiving exclusive breastfeeding in 2020 is 66.06% (exceeding the 2020 Strategic Plan target of 40%). The coverage of infants receiving exclusive breastfeeding in Central Sulawesi in 2020 is 61.9%. Although the coverage of infants receiving exclusive breastfeeding exceeds the strategic plan target, counseling related to exclusive breastfeeding must still be carried out, because reduced breastfeeding will affect the growth and development of human resources in the future. The Purpose of this community service is to increase mother's knowledge about exclusive breastfeeding. Methods: outreach activities were carried out to 30 breastfeeding mothers in Loru village using leaflets and banners about exclusive breastfeeding. Results: there is an increase in mother's knowledge about exclusive breastfeeding, where breastfeeding mothers want to give their babies exclusively breast milk. The counseling material was conveyed well, as long as the counseling participants were very active and enthusiastic in the question and answer session, the participants felt happy with this counseling, it was hoped that after counseling on exclusive breastfeeding, the baby's needs during the first 6 months after birth could be met.